Six feet deep dish - Quigley, Mindy (Quigley, Mindy. Deep dish mysteries, 2022)
"When, right before opening her new gourmet deep-dish pizzeria in Geneva Bay, Wisconsin, Delilah O'Leary is dumped by her fiancé and her aunt is accused of murder, she must save her pie-in-the-sky ambitions before they can even get off the ground"--